The Relationship between Money, Inflation, Banking Sector Development and Economic Growth: Case Study of the Republic of Turkey - Wilson, Sam Theophilus (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This research applied the four steps test model to investigate the relationship between money (M2), inflation (ICP) and banking sector development (DC) on economic growth (GDP) using Turkey as a case study. The annual data from 1960-2014 was extracted from the World Bank Development Indicator and used for the purpose of this empirical analysis. The unit root test of ADF and PP show that all of the variables are integrated order of I(1). The Johansen co-integration test shows that there exist cointegration between the variables and the vector error correction test show that there is along-run and short-run relationship between the variables. The Granger causality test indicates that there is a bi-directional relationship between economic growth (GDP) and money (M2), a unit directional relationship from banking sector development (DC) to economic growth (GDP) and a unidirectional relationship from inflation (ICP) to banking sector development (DC). However, we found no relationship between inflation (ICP) and economic growth (GDP).

ÖZ: Bu kağıt para (M2), enflasyon (ICP) ve ekonomik büyüme (GSYİH) Türkiye'de bir vaka çalışması olarak kullanarak Bankacılık Sektörü geliştirme (DC) arasındaki ilişkiyi araştırmak için dört adım test modeli uygulanır. 1960-2014 yıllık verilerden Dünya Bankası kalkınma gösterge çıkarılan ve bu araştırma amacıyla kullanılır. Birim kök testi ADF ve PP Haritayı tüm değişkenlerin bir I(1) entegre sırasını vardır, Johansen eş entegrasyon testi cointegration değişkenler arasında mevcut ve vektör hata düzeltme test göster değişkenler arasında uzun vadede ve kısa vadede bir ilişki olduğunu gösterir. Son test Granger Nedensellik testi ekonomik büyüme (GSYİH) ve para (M2), Bankacılık Sektörü geliştirme (DC) ekonomik büyüme (GSYİH) gelen bir birim yönlü ilişki ve Bankacılık Sektörü geliştirme (DC) için enflasyon (ICP) gelen bir birim yönlü bir ilişki arasında bir çift yönlü ilişki olduğunu gösterir. Ancak, hayır bulundu.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2016. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Banks and Banking--Turkey; Money Supply; Inflation; Banking Sector Development and Economy Growth